Barreiras para a prática de atividade física em indivíduos após acidente vascular encefálico - Bruna Debora Pacheco (2018)
Objective: To identify the barriers to physical activity in stroke survivors in the subacute phase and with mild functional disability, and the associated factors. Methods: A cross-sectional observational study, descriptive and exploratory was conducted, where barriers to physical activity were identified through Exercise Benefits / Barriers Scale (EBBS-Brasil) and questioning other possible barriers. We also investigated the association of barriers, identified by EBBS, with age, functional capacity, level of physical activity, socioeconomic level and depressive symptoms. Results: The sample consisted of 95 individuals with mean age of 62.9 (12.6) years and time after injury of 4 (0.8) months. The most frequent EBBS barriers scale items were fatigue (75.8 and 71.5%), reduced number of places to practice physical activity (61.1%) and distance from sites (50.6%). The most important additional barriers were the need for practical help (51.6%) and not knowing how to practice physical activity (47.4%). Barriers were significantly associated with socioeconomic status and depressive symptoms and explained 9% of the variance in the EBBS scores (p <0.01). Conclusion: Effort fatigue, the reduced number of places to practice and great distances from the places of physical activities were the most frequently reported barriers to physical activity. Depressive symptoms and socioeconomic level were variables that explained the variance in the EBBS scores. The rehabilitation of individuals after stroke, even those with mild functional disability, should include education in relation to the reduction of effort fatigue through the practice of early and continuous physical activity, orientation in relation to the existing places for the practice and how to practice physical activity without structured environments, besides the investigation and approach of depressive symptoms and socioeconomic factors.